Computer based ECG analysis: Visual programming of automated ECG analysis - Muhamad Syukri bin Ani (2023)
Computer Based ECG analysis is computerized calculation system that should automatically detected the important parameters of a given ECG reading. These parameters are very critical for a doctor to determine the problem of a patient heart, the identification of the specific area of the heart that is facing problem, the patient heart condition and what action should be taken to save the patient life.